Mechanics of Time-Dependent Materials and Processes in Conventional and Multifunctional Materials, Volume 3 Proceedings of the 2011 Annual Conference on Experimental and Applied Mechanics - Proulx, Tom.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Mechanics of Time-Dependent Materials and Processes in Conventional and Multifunctional Materials represents one of eight volumes of technical papers presented at the Society for Experimental Mechanics Annual Conference & Exposition on Experimental and Applied Mechanics, held at Uncasville, Connecticut, June 13-16, 2011. The full set of proceedings also includes volumes on Dynamic Behavior of Materials, Mechanics of Biological Systems and Materials; MEMS and Nanotechnology; Optical Measurements, Modeling and, Metrology; Experimental and Applied Mechanics, Thermomechanics and Infra-Red Imaging, and Engineering Applications of Residual Stress.
Using Remendable Polymers for Aerospace Composite Structures -- Study of the Effect of Interface Enthalpy on Nanocomposite Viscoelasticity -- Sterilization Effect on Structure, Thermal and Time-dependent Properties of Polyamides -- Microstructural Evolution of Nafion During Uniaxial Deformation Monitored by X-ray Scattering -- Coupled Non-fickian Diffusion and Large Deformation of Hydrogels -- Accelerated Testing Methods for Oxidative Aging of Polymeric Composites -- Degradation of Shape Memory Polymer Due to Water and Diesel Fuels -- Structural Enhancement of Framing Members Using Polyurea -- Keynote Presentation (40 minutes) -- Experiments and Models for the Time Dependent Mechanics of Nanoscale Polymeric Structures and Nanocrystalline Metal Films -- Study of Damage Evolution in High Strength Al Alloys Using X-ray Tomography -- Corrosion Behavior of SS 304 With Ball Milling and Electrolytic Plasma Treatment in NaCl Solution -- Experimental Studies of Phase Transformation in Shape Memory Alloys -- Measurement of Energy Loss in Thin Films Using Microbeam Deflection Method -- Multiscale Characterization of Water-, Oil- and UV-conditioned Shape-memory Polymer Under Compression -- Shape Memory Polymer Based Cellular Materials -- Influence of Mechanical Properties and Loading Conditions on the Recovery of Shape Memory Polymers -- Fatigue Cycling of Shape Memory Polymer Resin -- Higher Rate Testing of Long Fiber Filled Polypropylene -- Characterization of Elastomeric Composite Materials for Blast Mitigation -- Experimental Arrangement for Measuring the High-strain-rate Response of Polymers Under Pressures -- Simulation of Impact Tests on Polycarbonate at Different Strain Rates and Temperatures -- Experimental Investigation of Dynamic Mechanical Properties of Polyurea-fly Ash Composites -- Damage & Fracture of High-explosive Mock Subject to Cyclic Loading -- An Evaluation of A Modified Iosipescu Specimen for Measurement Of Elastic-plastic-creep Properties of Solder Materials -- Temperature Effect on Poisson$1 (Bs Ratio of Woven Composites -- Detection and Damage Monitoring in Composite Structures Using Piezoelectrics -- Representative Volume Element Analysis for the Evaluation of Effective Material -- Properties of Fiber and Particle Loaded Composites With Different Shaped -- Inclusions -- Stress-based Modeling of Composite Materials -- Time Dependent (Creep) Deformation of Thin Elastomers at Cold Temperature and Effective Strain Analysis of Their Laminates -- Time and Temperature Response of Composite Overwrapped Cylinders -- High Temperature, Non-contact, Electro-magnetic Mechanical Apparatus for Creep Testing -- Experiments and Predictions of Large Deformation and Failure in Thermomechanical Loading Environments -- Compliance Plot Analysis of Nonlinear Response of PMMA During Nanoindentation -- An Incremental Formulation for the Linear Analysis of Viscoelastic Beams: Relaxation Differential Approach Using Generalized Variables -- Modeling the Nonlinear Viscoelastic Behavior of Polyurea Using a Distortionmodified Free Volume Approach -- An Incremental Constitutive Law for Damaging Viscoelastic Materials -- Reliability Analysis of Mixed Mode Cracking With Viscoelastic Orthotropic Behaviour -- Long-term Life Prediction of CFRP Structures Based on MMF/ATM Method -- Non-local Solutions to Direct and Inverse Problems in Mechanics: A Fractional Calculus Approach -- Study on Crystallinity Dependency of Creep Deformation on GFRTP of Polyoxythlene (POM) -- Numerical Simulation of hot Imprint Process of Periodical Lamellar Microstructure Into Polycarbonate -- Rapid Characterization of Visco-elastic Properties of Polymeric Materials -- Estimation of Fatigue Life of Cortical Bone Considering Viscoelastic Properties and Damage Mechanics -- Crack Initiation and Viscoplasticity in Polyethylene Joint Replacement Components.s
Keywords: Engineering; Mechanics; Mechanics, applied; Surfaces (Physics).; Engineering; Theoretical and Applied Mechanics; Characterization and Evaluation of Materials; Mechanics